Understanding the Design Principles of Advanced Aqueous Zinc‐Ion Battery Cathodes: From Transport Kinetics to Structural Engineering, and Future Perspectives. Issue 45 (16th October 2020) - Yong, Bo; Ma, Dingtao; Wang, Yanyi; Mi, Hongwei; He, Chuanxin; Zhang, Peixin
Abstract: Rechargeable aqueous zinc‐ion batteries (AZIBs) have attracted extensive attention and are considered to be promising energy storage devices, owing to their low cost, eco‐friendliness, and high security. However, insufficient energy density has become the bottleneck for practical applications, which is greatly influenced by their cathodes and makes the exploration of high‐performance cathodes still a great challenge. This review underscores the recent advances in the rational design of advanced cathodes for AZIBs. The review starts with a brief summary and evaluation of cathode material systems, as well as the introduction of proposed storage mechanisms. Then, fundamental problems associated with ion and electron transport behaviors inside the electrode will be pointed out and followed by potential solutions, aiming to reveal the correlation between cathode architecture design and efficient transport kinetics through structural engineering. Afterward, the structural engineering for designing advanced cathodes, including interlayer intercalation, doping effects, defect engineering, surface coatings, composite formation, and morphology control, are summarized and discussed from the view of experimental and theoretical results. Finally, the critical research challenges and future perspectives on advanced cathode materials as well as the potential developing directions of AZIBs are also given. Abstract : This review highlights the recent progress on the rational design of aqueous zinc‐ion battery cathodes through structural engineering strategies, as well as discussing the role of engineering in tuning the structural properties of cathode materials. The critical challenges and opportunities in the future development of this field are also presented.